CASTING INTO ROLL CRYSTALLIZER OF HIGH-PRECISION CHLORINE-COPPER TAPE - E. F. Baranovski; V. M. ljushenko (Литьë и металлургия, 2005)
Analysis of the bowl-crystallizers diameter changing in the process of the belt casting is carried out. The bowlcrystallizers construction providing production of high-accurate casting is worked out.